Students’ Dilema in Subject Selection at Secondary Level - Saleem Taj; Sana; Abdul Quddoos; Kausar Hussain (Dialogue Social Science Review (DSSR), 2025)
The present study mainly aimed at knowing about “Choice of Subjects and the Related Problems of Secondary School Students.” It was a descriptive type of research. The researcher had the objectives including identifying the factors that influence students’ choice of subject at the secondary level. Also, for example to identify the influence of parental pressure, which amounts to a sort of problem in this regard. It was hypothesized that e.g. for the achievement of better results, students’ choice of selecting proper subjects is inevitable. A questionnaire with 13 items was used for data collection. Secondary schools of Distt: Mardan was the population of the study. A random sample of 400 students was selected. Science and arts students were separately analyzed. Some of the findings include but surely not limited to e.g. 46% of students (in wake of analysis of table VIII) had selected subjects which did not have relevance with their aspired and desired goals and hence the appearance of one of the problems related to students’ choice of subjects at the secondary level.